2019
DOI: 10.2196/13873
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Online Help-Seeking and Mental Health Difficulties: Systematic Narrative Review

Abstract: BackgroundYoung people frequently make use of the internet as part of their day-to-day activities, and this has extended to their help-seeking behavior. Offline help-seeking is known to be impeded by a number of barriers including stigma and a preference for self-reliance. Online help-seeking may offer an additional domain where young people can seek help for mental health difficulties without being encumbered by these same barriers.ObjectiveThe objective of this systematic literature review was to examine you… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
242
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(254 citation statements)
references
References 53 publications
(180 reference statements)
8
242
0
4
Order By: Relevance
“…However, as detailed below, a review of meta‐analytic work and narrative reviews, recent large‐scale public access and preregistered studies, and daily and momentary assessments of digital technology usage and mental health, show that that associations between time online and internalizing symptoms are often (a) mixed between positive, negative, and null findings, (b) when present, are likely too small to translate into practically or clinically meaningful effects (explaining less than 0.5% of the variance in symptoms with poor adjustment for relevant confounding factors and estimates that are virtually always derived from correlation designs), and (c) are typically not distinguishable in terms of likely cause and effect. In addition, a recent systematic narrative review of 28 studies of online help‐seeking behaviors indicated that many young people suffering from mental health problems are spending their time online searching for means of alleviating and better understanding their symptoms (Pretorius, Chambers, & Coyle, ).…”
Section: What Do We Currently Know About the Association Between Adolmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as detailed below, a review of meta‐analytic work and narrative reviews, recent large‐scale public access and preregistered studies, and daily and momentary assessments of digital technology usage and mental health, show that that associations between time online and internalizing symptoms are often (a) mixed between positive, negative, and null findings, (b) when present, are likely too small to translate into practically or clinically meaningful effects (explaining less than 0.5% of the variance in symptoms with poor adjustment for relevant confounding factors and estimates that are virtually always derived from correlation designs), and (c) are typically not distinguishable in terms of likely cause and effect. In addition, a recent systematic narrative review of 28 studies of online help‐seeking behaviors indicated that many young people suffering from mental health problems are spending their time online searching for means of alleviating and better understanding their symptoms (Pretorius, Chambers, & Coyle, ).…”
Section: What Do We Currently Know About the Association Between Adolmentioning
confidence: 99%
“…Young people report going online frequently to seek out health information (Kauer, Mangan, & Sanci, ) and, those with lower social and emotional well‐being, are more likely to report going online to seek support and to feel better about themselves (Rideout & Fox, ). Social networking sites may be used by young people in the face of setbacks (Toma & Hancock, ) and many young people turn to social media for support and advice related to their mental health symptoms (Pretorius et al, ), with some research suggesting that adolescents with moderate to severe depressive symptoms may be more likely (2×) than their peers to turn to social media for emotional support (Rideout & Fox, ).…”
Section: Overcoming Fears and Forging Future Directions For Adolescenmentioning
confidence: 99%
“…Given this context, mental health service providers have been asked to consider providing online resources as an 'adjunct to offline help seeking'. 5 Our service pages within the Trust website were aimed at professionals only, were difficult to find and did not give details about what to expect at a first assessment or how to travel to the clinic. The Trust website was awaiting redesign, but this wait had been some years with no clear date set.…”
Section: Problemmentioning
confidence: 99%
“…A large US study suggests that the vast majority (87%) of adolescents have gone online to seek information about mental health, while most (64%) have used a mental health app. 1 Social media is also endorsed by young people as a source of mental health advice, 35 especially for adolescents already struggling with moderate to severe depressive symptoms who, in one study, were more likely than their nondepressed peers to report using social media to access emotional support. 36 Given that the majority of youth in high-income countries are online, that youth are naturally turning to online spaces for information and support, and evidence-based mental health interventions are increasingly made available online, it seems that online platforms could be effectively mobilized to support youth mental health and respond in times of crisis.…”
Section: Can Digital Technologies Be Leveraged To Reach Vulnerable Yomentioning
confidence: 99%
“…A large US study suggests that the vast majority (87%) of adolescents have gone online to seek information about mental health, while most (64%) have used a mental health app. 1 Social media is also endorsed by young people as a source of mental health advice, 35 especially for adolescents already struggling with moderate to severe depressive symptoms who, in one study, were more likely than their nondepressed peers to report using social media to access emotional support. 36…”
Section: Can Digital Technologies Be Leveraged To Reach Vulnerable Yomentioning
confidence: 99%